THE ABRAHAM ACCORDS AND PEACE IN THE MIDDLE EAST: REGIONAL RECEPTION AND IMPLICATIONS - Henelito Jr Arias Sevilla (CMES (Center of Middle Eastern Studies), 2024)
The normalization of ties between Israel and four Arab countries (Bahrain, Morocco, the United Arab Emirates, and Sudan) starting in 2020 through the US-facilitated Abraham Accords opened a new paradigm of peace in the greater Middle East and North African region. Optimists embrace the Accords as the harbinger of a new era of Israel-Arab relations and a renewed opportunity for peace in the region. Others consider them as mere official pronouncements by involved parties and without regard to the urgent and long-standing Israeli-Palestinian conflict. This paper argues that the Abraham Accords are based solely on the national interests of the signatories and the facilitator, the United States, and not primarily intended for restoring Israel-Arab ties and regional peace and security. This paper begins by examining the prospects and challenges of peacebuilding in the Middle East. The discussion proceeds to the pragmatism of the Abraham Accords, i.e., its strategic advantages for the signatories and the U.S. Finally, the paper briefly explores the reception of relevant actors in the Middle East and the wider Asian region, particularly Saudi Arabia, Iran, Turkey, and China.